NSAIDs: can the presence of infectious agent influence the choice of analgesic drug? - О. А. Podpletnya; O. V. Khomiak; I. P. Koshova (Zaporozhye State Medical University, 2017)
Purpose. Considering the significant prevalence of comorbid pathology there is a high probability of NSAID use in patients with concomitant infection. In view of this screening of antimicrobial properties of their main groups was conducted for the purpose of selecting the most promising ones for further in-depth study. Materials and methods. The study of microorganisms' sensitivity was conducted using standard research methods - the method of "wells" and by determining the antibacterial properties of drugs, using tablets, based on the ability of the drug to diffuse into agar, used for sowing the test-culture. As the test cultures S. aureus, S. mutans, S. pyogenes, P. aeruginosa, E. Coli, isolated from patients who were treated in hospital were used. Predominant blocker of COX-1 (acetylsalicylic acid, ASA), nonselective blockers of COX-1 and COX-2 (ketorolac, diclofenac sodium, ibuprofen, mefenamic acid, dexketoprofen), predominant blockers of COX-2 (meloxicam and nimesulide), selective blockers of COX-2 (celecoxib), selective blockers of COX-3 (COX-1 in the brain) paracetamol and metamizole were tested. Results. The studies found that most of the tested NSAIDs have antimicrobial activity. Leader drugs in expressiveness of antimicrobial effects are drugs that have sufficient COX-1 (3) - activity: ASA, diclofenac, dexketoprofen, metamizole, and lesser extent - paracetamol. Tested NSAIDs showed the highest activity against gram-positive coccal flora, mostly affecting S. Pyogenes. Blockers of COX-3 paracetamol and metamizole, unlike other studied drugs, showed stronger antipseudomonal (both - moderate) and antistaphylococcal action (metamizole). Conclusions. NSAIDs with antimicrobial activity can potentially increase the activity of antiinfectious therapy. At the same time, the antimicrobial activity of NSAIDs, theoretically, can promote microbial resistance because of existence of microorganisms in a medium with subthreshold concentrations of drugs with antimicrobial activity. Considering this, further clinical and pharmacological research of this problem has a great practical importance.